Diagnosis and Management of Narcolepsy - Schneider, Logan; Mignot, Emmanuel (Seminars in Neurology, 2017)
Type 1 narcolepsy is caused by deficient hypocretin signaling in the central nervous system (CNS), and is distinct from other primary CNS hypersomnias, which seem to lay along a spectrum from type 2 narcolepsy to idiopathic hypersomnia. There appears to be a strong autoimmune diathesis to the development of type 1 narcolepsy, as evidenced by the near universal presence of HLA-DQB1*06:02 in patients. Growing knowledge of the immunogenetic basis of the disease is supported by genetic studies and seasonal variation of type 1 narcolepsy incidence following winter upper respiratory infections (e.g., strep throat and influenza). Despite improved diagnostic accuracy of adding cerebrospinal fluid hypocretin measurement to the traditional workup, recognition of the disorder remains limited by its moderate prevalence and atypical manifestations in different ethnic groups. Treatments are currently symptom-based, and have been extended to other hypersomnias with mixed results.
Keywords: narcolepsy; hypersomnia; neuroimmunology; sleep